1960
DOI: 10.1172/jci104044
|View full text |Cite
|
Sign up to set email alerts
|

The Existence of Ammonia in Blood in Vivo With Observations on the Significance of the Nh4+–nh3 System *

Abstract: The development of refined methods for determination of blood ammonia in the past 50 years has resulted in a gradual lowering of the reported concentrations in the peripheral venous blood of normal man (1). After extensive work with a microdiffusion technique, Conway and Cooke concluded that the normal in vivo peripheral venous level of the blood ammonia nitrogen in man was operationally zero, but that rapid liberation of ammonia from certain precursors occurred after shedding to produce in vitro values of abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1961
1961
2008
2008

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Use of either expression implies that only the free base diffuses in appreciable amounts across cell membranes and that diffusion, not active secretion, accounts for the movement of ammonia into both urine and peritubular blood. Values of PNH3 that we have observed are of the same order of magnitude as those observed by Bromberg, Robin, and Forkner (13). As a consequence of our studies on the intravenous infusion of ammonium lactate in dogs we have reached the following conclusions.…”
supporting
confidence: 88%
“…Use of either expression implies that only the free base diffuses in appreciable amounts across cell membranes and that diffusion, not active secretion, accounts for the movement of ammonia into both urine and peritubular blood. Values of PNH3 that we have observed are of the same order of magnitude as those observed by Bromberg, Robin, and Forkner (13). As a consequence of our studies on the intravenous infusion of ammonium lactate in dogs we have reached the following conclusions.…”
supporting
confidence: 88%
“…The (ammonia) of whole blood has therefore been calculated by multiplying all values for theoretical plasma (ammonia) by a factor representing the ratio of venous whole blood to plasma (ammonia). The value 1.4 has been assigned to this ratio; this is the value furnished in wrhat appears to be the most careful study reported (48), represents the mean o f values arrived at in four recent studies (28,(48)(49)(50), and is in accord with our own observations. Plasma (ammonia) was taken as 0.93 X plasma water (ammonia) (51).…”
Section: The Assumptionssupporting
confidence: 72%
“…Ammonia in blood even during extreme hyperammonemia exists primarily in the NH4+ form. The concentration of NH3 represents only a minute fraction of the total blood ammonia concentration (22), and in the present study is obviously of insufficient magnitude to explain the alterations in renal ammonia balance across the renal circulation during ammonium lactate infusion. It would seem likely, therefore, that the renal tubular cells removed significant quantities of NH4+ from the blood during these experiments.…”
Section: Methodsmentioning
confidence: 55%